Risk Factors for the Development of Hyaline Membrane Disease in Preterm Infants - Sudigdo Sastroasmoro (Paediatrica Indonesiana, 1998)
Hyaline membrane disease (HMO) is a respiratory disease commonly found in preterm infants. While this disease occurs as the result of surfactant deficiency which is a function of gestational age, certain maternal and neonatal factors play a role in the development of the disorder. Preterm infants born at the Department of Obstetrics and Gynecology, Cipto Mangunkusumo Hospital, Jakarta, between, March 1997 and May 1998 were studied for the development of HMO. It was concluded that antepartum hemorrhage, gestational age, sex, mod of birth, and the first minute Apgar score were associated with the development of HMD, while the use of contraceptives, early rupture of the membrane, maternal morbidity, and passive cigarette smoking were not.